beta-Amyloid precursor protein binds to the neurite-promoting IKVAV site of laminin. - Kibbey, M C (1993)
We previously characterized a 110-kDa membrane-associated laminin-binding protein (LBP110) from brain which binds the laminin A chain -Ile-Lys-Val-Ala-Val-(IKVAV) site and increases in injury. Here we demonstrate that antisera directed against different epitopes of beta-amyloid precursor protein (APP) recognize LBP110 and that APP is recognized by LBP110 antiserum. APP specifically binds IKVAV and not another biologically active laminin-derived peptide containing the amino acid sequence -Tyr-Ile-Gly-Ser-Arg-. PC-12 cells transfected with antisense APP RNA produce less APP and LBP110, and they form fewer processes when cultured on either laminin or the IKVAV peptide. Thus, LBP110 is a member of the APP family and a function for APP in neurite outgrowth is now defined.